A study of effect of Helicobacter pylori on hematological parameters in Ubari, Libya - Hanan. A. Alhaddad; Rabiya. M. Eshaewi; Hajer. I . Almobarak (Journal of Pure & Applied Sciences, 2022)
Helicobacter pylori bacteria are a common bacterium and have an effect on many patients. This study was conducted on 80 samples of patients and healthy people in the area of Ubari,Libya to determine the effect of bacterial infection on hematological parameters. IgG antibodies have also been detected for H. pylori bacteria, which can be the cause of anemia. This study showed that the arithmetic mean values of the healthy and patient samples were all within the normal range, except the average MCHC for healthy subjects, where it was lower than normal. The statistical analysis of these samples showed significant differences in RBC, MCH, and MCHC, but there were no significant differences in other hematological parameters where the value of (P-value >0.05). In addition, it was found through the statistical analysis of healthy and patient females, the presence of significant differences in RBC, MCH, and MCHC. Significant differences after statistical analysis of category T-healthy males and male patients with all values showed no significant differences between the two groups. The results showed that H. pylori infection had an effect on the hematological parameters related to erythrocytes. The effect was more pronounced in females than in males, but this effect was minimal.